Protective SARS-CoV-2 Antibody Response in Children With Inflammatory Bowel Disease - Bosa, Luca; Di Chiara, Costanza; Gaio, Paola; Cosma, Chiara; Padoan, Andrea; Cozzani, Sandra; Perilongo, Giorgio; Plebani, Mario; Giaquinto, Carlo; Donà, Daniele; Cananzi, Mara (Frontiers in Pediatrics, 2022)
Background. To date, there’s no evidence of an increased risk of SARS-CoV-2 infection or more severe COVID-19 in patients with inflammatory bowel disease (IBD). However, whether COVID-19 alters the clinical course of IBD or whether IBD treatment affects the immunological response to SARS-CoV-2 is still under investigation, especially in children. Aim. To assess the serological response to SARS-CoV-2 in children with IBD, and to evaluate the impact of COVID-19 on the clinical course of IBD. Material and methods. This prospective study enrolled children (0-18 years) followed-up at the University Hospital of Padova for IBD, who acquired a confirmed SARS-CoV-2 infection between 02.2020 and 02.2021. The anti-SARS-CoV-2 S-RBD IgG titer was evaluated at three months after infection and compared to that of a control group of healthy children matched for age, sex, and COVID-19 severity. Results. Twelve children with IBD (M=5; median age 14 years) contracted COVID-19 during the study period. 11/12 patients were under immunomodulatory treatment (4/12 steroids; 6/12 azathioprine; 3/12 anti-TNFs; 2 vedolizumab; 1 ustekinumab). SARS-CoV-2 infection remained asymptomatic in 4/12 children and caused mild COVID-19 in the remaining 8. Mean anti-SARS-CoV-2 IgG S-RBD titer was similar between IBD patients and controls (27.343.8 vs. 36,835.3 kAU/L, p=ns). No children experienced IBD flares nor required gastroenterological support during the infection period. Discussion. Children with IBD can mount a protective humoral response against SARS-CoV-2, which is comparable to that of their healthy peers regardless of ongoing immunomodulatory treatment. This study also supports the favorable course of PIBD during COVID-19 and vice-versa.